The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1007/s00330-002-1431-1
|View full text |Cite
|
Sign up to set email alerts
|

Use of multidetector row CT with volume renderings in right lobe living liver transplantation

Abstract: Multidetector row CT is a feasible diagnostic tool in pre- and postoperative liver partial transplantation. We can assess vascular anatomy and liver parenchyma as well as volumetry, which provide useful information for both donor selection and surgical planning. Disorders of the vascular and biliary systems are carefully observed in recipients. In addition, we evaluate liver regeneration of both the donor and the recipient by serial volumetry. We present how multidetector row CT with state-of-the-art three-dim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 18 publications
0
13
0
1
Order By: Relevance
“…With MDCT, thin slices can be obtained with excellent temporal resolution and precise 3D models can be created. Recently, MDCT volumetry of the donor of partial liver grafts, with manual or automatic processing 3D techniques, proved to be accurate [21] and liver CT angiography has become a substitute for invasive angiography [22]. Moreover, the relationship of the vasculature with anatomical structures, like the gallbladder, can be clearly visualized by simultaneous display, like that proposed here.…”
Section: Discussionmentioning
confidence: 89%
“…With MDCT, thin slices can be obtained with excellent temporal resolution and precise 3D models can be created. Recently, MDCT volumetry of the donor of partial liver grafts, with manual or automatic processing 3D techniques, proved to be accurate [21] and liver CT angiography has become a substitute for invasive angiography [22]. Moreover, the relationship of the vasculature with anatomical structures, like the gallbladder, can be clearly visualized by simultaneous display, like that proposed here.…”
Section: Discussionmentioning
confidence: 89%
“…It has recently been shown that volumetric assessment of tumor burden gives different results for treatment response than long-axis or bi-dimensional measurements; thus, in the near future volumetric measurement techniques may be employed for accurate quantification of tumor burden (Saini [19], presented at the Radiological Society of North America, December 2001). Volume rendering with multidetector-row CT has also recently been utilized in planning partial liver transplantation [20].…”
Section: Discussionmentioning
confidence: 99%
“…Since impaired liver function after resection and transplantation is caused by insufficient liver volume [1], a reliable volumetric assessment of the hepatic segments of potential living donors is one of the key factors in the preoperative donor evaluation. Recently, preoperative liver volumetry based on CT volume data sets resulted in significantly improved clinical outcome [2,3,4]; however, these procedures require an arbitrary definition of the potential resection line along the middle hepatic vein and are therefore relatively operator dependent. Although several refinements in semi-automatic liver volumetry have been introduced, leading to individualised computer-generated resection protocols [5], there is no report concerning automatic liver segmentation and volumetry on the basis of the intrahepatic portal venous blood supply.…”
mentioning
confidence: 99%